Movement Patterns of African Elephants (Loxodonta africana) in a Semi-arid Savanna Suggest That They Have Information on the Location of Dispersed Water Sources - Wato, Yussuf A.; Prins, Herbert H. T.; Heitkönig, Ignas M. A.; Wahungu, Geoffrey M.; Ngene, Shadrack M.; Njumbi, Steve; van Langevelde, Frank (Frontiers in Ecology and Evolution, 2018)
Water is a scarce resource in semi-arid savannas where over half of the African elephants (Loxodonta africana) populations occur and may therefore influence their movement pattern. A random search is expected for an animal with no information on the location of the target resource, else, a direction-oriented walk is expected. We hypothesized that elephants movement patterns show a stronger directional orientation towards water sources in the dry season compared to the wet season. We investigated the movement paths of four male and four female elephants with hourly GPS fixes in Tsavo National Park, Kenya in 2012-2013. Consistent with our predictions, the movement paths of elephants had longer step lengths, longer squared net displacements, and were directed towards water sources in the dry season as compared to the wet season. We argue that African elephants know the location of dispersed water resources, enabling them to survive with scarce resources in dry savannas. These results can be used in conservation and management of wildlife, through for instance, protection of preferred water sources.